Delayed seroreversion of specifical antibody against HIV in HIV‐exposed infants: A retrospective cohort study. Issue 11 (25th December 2020) - Liu, A; Zhang, L; Zhang, X; Zhang, HW; Tian, YM; Li, JW; Li, QY; Shao, Y; Ye, JZ; Li, ZC; Wang, H; Sun, LJ
Abstract : Objectives: To investigate the seroreversion time in HIV‐1‐exposed but uninfected infants from two tertiary hospitals in China. Methods: This study retrospectively investigated the data of perinatal, HIV‐1‐exposed infants from hospitals in Beijing and Shenzhen. Maternal and infant medical records from both hospitals from January 2009 to December 2019 were reviewed, and the HIV antibody seroreversion times of infants were determined. From 2009 to 2019, a total of 485 HIV‐1‐exposed but uninfected infants were enrolled. The majority of infants were born at term with normal birth weight. Results: The seroreversion rates were 89.3%, 94.2% and 100% at 12, 18 and 24 months of age, respectively. There were no significant associations between seroreversion and several risk factors, such as gender, birth weight, gestational age, mode of delivery, postpartum prophylaxis and antiretroviral treatment duration. The mean value of HIV‐specific immunoglobulin G concentration decreased from 15.4 at day 42 to 0.03 after 24 months in HIV‐exposed, uninfected infants. Conclusions: Clearance of HIV antibodies could take more than 18 months in a small number of perinatally exposed infants. Caution should be used in excluding or diagnosing perinatal HIV infection in children with long persistence of HIV antibodies.